2004
DOI: 10.4102/ojvr.v71i4.252
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary survey of ticks (Acari : Ixodidae) on cattle in northern Sudan

Abstract: , the geographical distribution of ticks on cattle in the Sudan was determined. Seventeen locations were surveyed from Northern, Central, Eastern, Western, Blue Nile and White Nile Provinces. Total body collections of ticks were made from 20 cattle at each location. Four tick genera and 11 species were identified. The tick species collected included Amblyomma lepidum, Amblyomma variegatum, Boophilus decoloratus, Hyalomma anatolicum anatolicum, Hyalomma dromedarii, Hyalomma impeltatum, Hyalomma marginatum rufip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 10 publications
4
27
1
Order By: Relevance
“…Rhipicephalus appendiculatus was absent from the study sites, although the specie was found in other areas of the Eastern Cape, as shown by other studies(Muchenje et al 2008a, b;Nyangiwe et al 2011;Marufu et al 2011b). Species variations in the current study were in line with the reports bySalih et al (2004),Gashaw and Tessema …”
supporting
confidence: 94%
“…Rhipicephalus appendiculatus was absent from the study sites, although the specie was found in other areas of the Eastern Cape, as shown by other studies(Muchenje et al 2008a, b;Nyangiwe et al 2011;Marufu et al 2011b). Species variations in the current study were in line with the reports bySalih et al (2004),Gashaw and Tessema …”
supporting
confidence: 94%
“…The finding that Northern and Central Sudan had a high risk of infection with T. annulata could be justified by the fact that the principle tick vector H. anatolicum anatolicum is present in these regions as the predominant tick species all year round (Anonymous 1983;Salih et al 2004;Ahmed et al 2005). The same justification could apply to Eastern and Western Sudan and White Nile, where a low risk or no risk was reported and where the principle tick vector H. anatolicum anatolicum does not exist (Anonymous 1983;Salih et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The same justification could apply to Eastern and Western Sudan and White Nile, where a low risk or no risk was reported and where the principle tick vector H. anatolicum anatolicum does not exist (Anonymous 1983;Salih et al 2004). The antibodies profile was found to increase significantly with advance in age, and thus the age of the animal could be a risk factor for acquisition of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Grazing is limited to seasonal watercourses and low-lying areas following sporadic rain showers. Hyalomma anatolicum ticks have been detected in the River Nile state, where 74 % of the ticks feeding on sheep were found to be H. anatolicum (Salih et al, 2004;Ahmed et al, 2005).…”
Section: Study Site and Parasite Samplesmentioning
confidence: 99%